U.S. Treasury market functioning from the GFC to the pandemic - Tobias Adrian; Michael J. Fleming; Kleopatra Nikolaou (Federal Reserve Bank of New York, 2025)
This article examines U.S. Treasury securities market functioning from the global financial crisis (GFC) through the Covid-19 pandemic given the ensuing market developments and associated policy responses. We describe the factors that have affected intermediaries, including regulatory changes, shifts in ownership patterns, and increased electronic trading. We also discuss their implications for market functioning in both normal times and times of stress. We find that alternative liquidity providers have stepped in as constraints on dealer liquidity provision have tightened, supporting liquidity during normal times, but with less clear effects at times of stress. We conclude with a brief discussion of more recent policy initiatives that are intended to promote market resilience.
Keywords: G12; G24; G28; 330; intermediation; liquidity; regulation; market structure; Treasury securities